PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN KREATIVITAS PADA ANAK USIA DINI - Elsa Nurfuady; Heris Hendriana; Ghina Wulansuci (IKIP Siliwangi, 2019)
Basically humans have had creative potential since he was created. With the potential of its natural creativity, it is expected that early on, children will need activities related to creative ideas through coaching so that children can develop their creative potential optimally. For that we need a learning method that can improve children's creativity, one of which is the experimental method. Through the experimental method children can be trained in developing creativity. The purpose of this study is to examine the achievement of children's creativity in using experimental methods. This study used a quasi-experimental method with Nonequevalent Control Group Design research design using two classes consisting of B1 experimental group and B2 control class at Al-Masruroh Kindergarten. Based on data processing and research results obtained the results of the pre-test showed that there were no significant differences between the experimental group and the control group (TK Al-Masruroh) with p-value> 0.05 which was 0.145> 0.05, while the post test results showed creativity after the application of the experimental method there is a significant difference with the value of pvalue <0.05 which is the result of 0.000 <0.05. Based on the results of this study, the researcher recommends to child educators that the experimental method can be used as one of the learning methods to improve children's creativity.